THE RISE OF DIGITAL ART - Gupta, Sonali (International Journal of Research -GRANTHAALAYAH, 2019)
The medium of digital art has existed for over a hundred years, but it’s only now that it’s getting the spotlight. Technology is a means of actions. Like a pencil or a canvas. Digital technology is the latest of a series of tool used by artist. According to digital artist “To me, my mouse, keyboard and text editor or DAW are what a paint brush palette and canvas would be to a painter. Traditional art workflow can be emulated in the digital domain or be augmented with digital practices. Digital art is defined as artistic works that utilized digital technology as part of the creative process.